Об удельной упругой энергоемкости пород земной коры Украины - Гордиенко, В.В. (Геофизический журнал, 2012)
Розглянуто величини питомої пружної енергоємності порід земної кори України на глибині 10 км. Приблизно на цій глибині розміщуються більшість джерел землетрусів. Параметр змінюється у межах (1,3—1,8) 10⁶ Дж/м³. Варіації пов’язані переважно з температурою порід. Визначено, що питома пружна енергоємність добре узгоджується із сейсмічним моментом та об’ємом джерела. The values of specific elastic energy-capacity of the earths crust rocks of Ukraine are examined at the depth of 10 km. Most earthquake foci are approximately at this depth. The parameter varies between (1,3—1,8) 10⁶ J/m³. The variations are mainly related to the temperature of rocks. It is shown that specific elastic energy capacity is in good agreement with the seismic moment and volume of the seismic focus.